Development Of Flash Card Applications Based On Ngada Local Culture To Improve Understanding Of Geometry Concepts For Children Aged 4-5 - Nafsia, Andi; Fono, Yasinta Maria; Radha, Maria Anna Ghena (Jurnal Smart Paud, 2024)
The research aims to: 1) to know the description of the needs analysis of the media to improve the Understanding of Geometry Concepts of Early Childhood, 2) to produce a Flash Card Application Based on Ngada Culture to Improve Understanding of Geometry Concepts of Early Childhood. The development of flash card applications based on Ngada local culture was developed using a development research model with a teaching material development model, namely the Rowntree model. The Rowntree development model consists of 3 stages, namely the planning stage, the development stage, and the evaluation stage. The subjects of this study were teachers and 15 children at Citra Bakti Integrated PAUD. The results of the Ngada culture-based Flash Card Application development research for expert trials and students as product users are as follows: (1) the quality of flash card applications based on Adobe Flash ver.6 media for the feasibility of material content based on material expert trials is in the ‘valid’ category, (2) the quality of applications based on the results of learning design expert trials is in the ‘valid’ category, (3) the quality of flash card applications based on the results of language expert trials is in the ‘valid’ category (4) the quality of flah card applications based on the results of individual trials is in the ‘valid’ category (5) the quality of flash card applications based on the results of small group trials is in the ‘valid’ criteria. Based on the results of the application validation test, it is declared feasible to use.